Launch of MSDN magazine in the Asia-Pacific region and the investigation of the direct marketing efforts. - Lee, Yee Yern. (2008)
This paper will revolve around the launch of MSDN Magazine in the Asia-Pacific and the examination of the various aspects of the direct marketing campaign to determine its effectiveness.